Implementing Debate To Improve The Speaking Skill Of The Eleventh Grade Students Of SMK 17 Agustus 1945 Muncar Banyuwangi - Ridwan Ridwan (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2017)
This study aims to improve students' speaking skills by applying the debate. Classroom action research (CAR) aims to find teaching and learning strategies that match the style of the learner and to solve teacher problems in finding the right techniques in teaching. Research conducted in SMK 17 August 1945 Muncar Banyuwangi on 39 students of class XI AK1 done in two cycles with stages of planning, implementation, observation, and reflection. Instruments used for data collection are observation sheets, questionnaires and student opinions about the debate. The teaching and learning procedure is divided into three steps; pre-activity, main activity, and post activity. Researchers found that the application of debate can improve students' speaking skills